Analysis of Implementation of the 2013 Curriculum in Elementary School on Teacher’s Capabilities in the Field of Pedagogic Competence - Herlina, Lina; Nuryani, Pupun; Suyitno, Y. (International Conference on Elementary Education, 2022)
This research is motivated by the low quality of teachers in Indonesia. Whereas the aspect of the ability of teachers is one of the success factors of Indonesian education. One of the problems that arise in the 2013 curriculum is that the teacher does not understand the process of implementing authentic learning and assessment in the implementation of the 2013 curriculum. This study aims to describe the pedagogic competence of the teacher's ability. The method used in this research is case study. The data collected through the primary study are Pedagogic Competence books and other books as support. The data is processed through data reduction, data presentation and verification. The results of this study indicate that (1) the teacher's ability to develop the curriculum is in line with pedagogic competence (2) the teacher's ability to carry out assessments and evaluations is not yet in line with pedagogic competence in conducting evaluations. The result is that there is a relevance between the ability of teachers and pedagogic competence in Government Regulation No. 16 of 2007.